Judicial Oversight as a Guarantee for the Implementation of Insurance Confiscation Decisions in Administrative Contracts - Tawfeek, Nawar N. (PROSPECTIVE RESEARCHES, 2025)
The administration has the authority to issue decisions necessary for conducting its administrative activities. These decisions serve as a tool that reflects the administration’s ability to impose rights and obligations independently of the will of other parties. Such decisions constitute unilateral legal acts that have direct effects on legal positions as soon as they are issued. Moreover, the administration enjoys the privilege of immediate enforcement of its decisions without needing to resort to the judiciary, which grants it exceptional powers. In the context of administrative contracts, the administration may collect financial guarantees stipulated in the contract or compel contractors to fulfill their obligations through legal coercive measures—whether administrative or criminal penalties—within the limits and conditions prescribed by law. Insurance (or guarantees) can thus be conceived as a financial commitment undertaken by the contractor to demonstrate seriousness and competence in fulfilling contractual obligations. It serves as a protective shield for the administration, functioning as an essential mechanism to safeguard its interests and affirm the seriousness of project implementation. These financial deposits are not merely indicators of the bidder's commitment, but also serve as a strong reassurance to the administration, guaranteeing its rights in the event of non-compliance or breach of the agreed-upon terms and procedures.